Elementary School Students’ Mathematics Problem-Solving Skills through Teams Games Tournament Assisted by Number Mystery - Nanda Tri Yuliana; Hesti Yunitiara Rizqi (Darul Yasin Al Sys, 2026)
Mathematical problem-solving remains challenging for elementary school students, particularly in understanding problem information, selecting appropriate strategies, executing solution procedures, and evaluating answers. This study aimed to examine differences in mathematical problem-solving skills between students taught through Teams Games Tournament (TGT) assisted by Number Mystery and those receiving conventional instruction, as well as to determine the effect of the intervention on students’ performance. A quasi-experimental method with a nonequivalent control group design was employed, involving 63 third-grade students comprising 32 students in the experimental group and 31 students in the control group. The intervention was implemented over three instructional meetings. Data were collected through pretests, posttests, questionnaires, observations, student worksheets, and documentation and analyzed using the Shapiro–Wilk test, Levene’s test, an independent-samples t test, and simple linear regression. The findings showed that the experimental group achieved a higher mean posttest score than the control group (85.47 vs. 71.13), with a statistically significant between-group difference, t(61) = 9.433, p < 0.001. Regression analysis yielded R = 0.770 and R² = 0.593, indicating that the intervention accounted for 59.3% of the variance in students’ mathematical problem-solving performance. These findings demonstrate that TGT assisted by Number Mystery effectively enhances elementary students’ mathematical problem-solving skills. The integration of cooperative learning activities, academic games, and concrete instructional media provides a practical pedagogical alternative for supporting students in understanding problems, formulating strategies, implementing solutions, and evaluating their results.